AN ANALYSIS OF ILLOCUTIONARY ACTS USED IN AKEELAH AND THE BEE MOVIE - Alvia Merry Mariani; Endang Susilawati; Urai Salam (﻿Kantor Bahasa Provinsi Bangka Belitung, 2023)
This research was investigating one of speech acts skills in communication that is illocutionary acts. Therefore, the aim of this study was to achieve three objectives, the first is to identify the classifications of illocutionary acts performed in the conflict storyline of Akeelah and The Bee movie. The second is to find out the types of illocutionary acts which are dominantly expressed in Akeelah and The Bee movie. The last is to identify the types of sentences of indirect speech acts to represent the five types of illocutionary acts. To achieve these objectives, a pragmatic analysis was implemented. Therefore, the research used the theory of speech acts proposed by Yule (2014). The data collected through a purposive sampling, a corpus (transcript of the movie), and a movie. In the three conflict storylines process of data analysis was started by watching the movie and reading the whole script. The next is classifying the data based on the types of illocutionary acts proposed by Yule and the last step was interpreting the data based on the contextual meaning of the utterances from the characters. As a result, three points of conclusions are concluded. The first, the classifications of illocutionary acts found were directive, representative, commissive, and expressive. The second, the most dominant types of illocutionary acts were representative and expressive (37%), the middle was directive (27%), and the less was commissive (9%). The three main characters performed illocutionary acts both in direct speech or indirect speech. The indirect speeches were dominated by interrogative sentences.